1999
DOI: 10.1007/s002449900506
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and Subchronic Physiological Effects of Waterborne Iron Overload on Whitefish Exposed in Humic and Nonhumic Water

Abstract: One-year-old whitefish, Coregonus lavaretus, were exposed to three types of iron-rich water, two dilutions for each, in a subchronic (30-day) experiment. In natural iron-rich humic water, both the bioaccumulation and physiological effects of iron exposure were negligible. In humic-free water with high amount of additional inorganic iron (nominally 8 mg Fe/L), Fe accumulated in gills, liver, and gut. This accumulation was accompanied by decreased glycogen phosphorylase activities and microsomal EROD activity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Water pumped from a well is not likely to be encountered by fish very often in the natural world, except from the input of small streams headed by ground water. Further, well water is often higher in iron content; high iron content has been shown to cause physiological stress in some adult fish (Lappivaara, Kiviniemi, & Oikari, 1999). Therefore, it should not be surprising that fish should prefer lake water over well water.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…Water pumped from a well is not likely to be encountered by fish very often in the natural world, except from the input of small streams headed by ground water. Further, well water is often higher in iron content; high iron content has been shown to cause physiological stress in some adult fish (Lappivaara, Kiviniemi, & Oikari, 1999). Therefore, it should not be surprising that fish should prefer lake water over well water.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…Several authors have demonstrated iron accumulations in different organs such as the liver and gut (Lappivaara et al 1999) and precipitation on gill epithelium causing gill clogging and damage (Dalzell and Macfarlane 1999;Peuranen et al 1994). Iron has been shown to reduce oxygen uptake by fish (Peuranen et al 1994), modified blood parameters (Brenner et al 1976;Lappivaara et al 1999;Lappivaara and Marttinen 2005;Peuranen et al 1994), decreased growth and disturbed fish reproduction (Sykora et al 1972;Smith et al 1973;Smith and Sykora 1976).…”
Section: Introductionmentioning
confidence: 96%
“…Fish can take up both forms from water through the gills (Bury and Grosell, 2003). However, excess waterborne iron is toxic to fish (Peuranen et al, 1994;Lappivaara et al, 1999;Dalzell and Macfarlane, 1999). Fe(II) in water is more toxic to fish than Fe(III) as the former is more soluble and easily absorbed (Vuori, 1995).…”
Section: Introductionmentioning
confidence: 97%